Student Teachers' Acceptance to Use Telegram Application in Distance Education Based on Technology Acceptance Model (TAM) (A Field Study on a Sample of Fourth-Year Students in the Faculty of Education at Tishreen University): (Damascus University Journal of educational and Psychologyical sciences, 2024)
This research aimed to determine the acceptance degree of student teachers to use the Telegram application in distance education. To achieve the research objectives, a descriptive approach was adopted, and the Technology Acceptance Model (TAM) was used to construct the research tool to measure the impact of the perceived ease of use factor on perceived usefulness, and then measure the impact of the two factors: (perceived ease of use and perceived usefulness) on attitude, followed by measuring the impact of the two factors: (perceived usefulness and attitude) on behavioral intention. The research sample consisted of (230) student teachers in the fourth-year, and the two researchers arrived at the following results:- The sample individuals' perception level of the ease of using the Telegram application in distance education, and its usefulness, is low, and they have negative attitudes, and low behavioral intentions towards using in the future.- The student teachers' perceptions of the ease of using the Telegram application in distance education positively affect their perceptions of its usefulness, and predict it.- Both (perceived ease of use and perceived usefulness) factors positively affect the student teachers' attitudes towards using the Telegram application in distance education.- Perceived usefulness has the greatest impact on predicting the student teachers' attitudes towards using the Telegram application in distance education, followed by perceived ease of use.- Both (perceived usefulness and attitude) factors positively affect the student teachers' behavioral intentions towards using the Telegram application in distance education in the future.- The attitude factor has the greatest impact on predicting the student teachers' behavioral intentions towards using the Telegram application in distance education, followed by perceived usefulness.Based on the research results, the two researchers provided some recommendations, such as enhancing student teachers' perceptions of the ease of use and usefulness of the Telegram application in distance education by including it in practical computer courses.
Keywords: Student Teachers; Telegram Application; Distance Education; TAM Model